Do Authentic Souvenirs and Co-created Shopping Experiences Enhance Shopping Satisfaction? Evidence from Indonesian Supermarket Tourism - Yustisia Pasfatima Mbulu; Fetty Nurmala Rossi; Vitha Octavanny (Centre of Excellence in Tourism Udayana University, 2026)
The phenomenon of supermarket tourism has emerged as a new dimension of contemporary tourism, yet research on supermarkets as providers of authentic souvenirs remains limited. This study aims to investigate the influence of souvenir authenticity and collaborative shopping experiences on tourist shopping satisfaction in Indonesia. Using a case study design at representative supermarkets in key destinations (Pasarina in Jakarta, Hokky in Surabaya, and Pepito and Bintang in Bali), the study employs a quantitative approach. Data were collected through purposive sampling from 200 domestic tourists and analyzed using Structural Equation Modeling (SEM-PLS) through SmartPLS 3.2.9. The findings indicate that souvenir authenticity and collaborative shopping experiences positively and significantly influence shopping satisfaction. These results suggest that supermarkets in Jakarta, Surabaya, and Bali are becoming culinary tourism destinations by curating authentic local products, such as artisan chocolate in Jakarta, culinary heritage products Spikoe and Blouder in Surabaya, and geographically based coffee and cocoa in Bali, while offering experiential activities. Managerial implications suggest that integrating local culture into modern retail strategies can enhance destination competitiveness.